Device and method for conducting diffusion dialysis and electrolysis electrodialysis integrated treatment on vanadium-alkali feed liquid in alkali method vanadium extraction process - LI CHUANRUN; WANG YAOMING; LI WEI; YAN HAIYANG; WU LIANG; ZHANG QIN (2016)
The invention discloses a device and method for conducting diffusion dialysis and electrolysis electrodialysis integrated treatment on vanadium alkali feed liquid in the alkali method vanadium extraction process. The device is characterized in that a retentate tank of a diffusion dialysis device is combined with an anode liquor tank of an electrolysis electrodialysis device, a dialysate tank of the diffusion dialysis device is combined with a cathode liquor tank of the electrolysis electrodialysis device, and the device for conducting integrated treatment on the vanadium-alkali feed liquid in the alkali method vanadium extraction process is formed; and primary separation is conducted on vanadium-alkali feed liquid through the diffusion dialysis device in the integrated treatment device, and retentate generated after diffusion dialysis is deeply separated through electrolysis electrodialysis. According to the method, in combination with the diffusion dialysis device which has the advantages of being large in t